Solvatochromic Behaviour of Some Thiourea Monophosphazene Derivatives - Arifien, A.E. (Asian Journal of Chemistry, 2010)
The electronic absorption spectra of 1-o-aryl-2, 2-di(1-o-aryl)-2-(N-o-aryl thiourea) monophosphazene derivatives were studied in mixed organic solvents. The spectra proved the formation of molecular complexes between solute and solvents for which the stability constant and heat of formation were determined. The behaviour of monophosphazenes have been also studied in aqueous-organic solvent mixtures at different pH. The pKa values of the compounds have been determined and discussed in relation to both the concentration and the nature of the organic co-solvent used.